Self-Assembled Nanostructures of Homo-Oligopeptide as a Potent Ice Growth Inhibitor - Kim, Yong Duk; Jung, Woo Hyuk; Ahn, Dong June; Lim, Dong-Kwon (American Chemical Society, 2023)
This study reports the formation of self-assembled nanostructures with homo-oligopeptides consisting of amino acids (i.e., alanine, threonine, valine, and tyrosine), the resulting morphologies (i.e., spherical shape, layered structure, and wire structure) in aqueous solution, and their potential as ice growth inhibitors. Among the homo-oligopeptides investigated, an alanine homo-oligopeptide (n = 5) with a spherical nanostructure showed the highest ice recrystallization inhibition (IRI) activity without showing a burst ice growth property and with low ice nucleation activity. The presence of nanoscale self-assembled structures in the solution showed superior IRI activity compared to an amino acid monomer because of the higher binding affinity of structures on the growing ice crystal plane. Simulation results revealed that the presence of nanostructures induced a significant inhibition of ice growth and increased lifetime of hydrogen bonding compared with unassembled homo-oligopeptide. These results envision extraordinary performance for self-assembled nanostructures as a desirable and potent ice growth inhibitor.